Surgical management of the elderly elbow - Gibbs, V; Middleton, R; Rees, J (Elsevier, 2016)
The elbow has a major role in helping with the positioning of the hand in space. Any pathology of the joint can result in pain, loss of function and difficulties with activities of daily living With an increasingly elderly population the degenerative conditions affecting the elbow are becoming more prevalent. Besides traumatic injury, the more commonly encountered problems are osteoarthritis, inflammatory arthritis, nerve compression and stiffness. An awareness of these conditions is important for those who provide care to this patient group. Whilst many of these conditions can be managed conservatively in primary care, some patients are referred to secondary care and elect for surgical treatments. This review considers the surgical treatments for the common elbow pathologies in the elderly population, including the potential complications associated with such treatments.